2013
DOI: 10.1073/pnas.1216197110
|View full text |Cite
|
Sign up to set email alerts
|

Parkin overexpression during aging reduces proteotoxicity, alters mitochondrial dynamics, and extends lifespan

Abstract: Aberrant protein aggregation and mitochondrial dysfunction have each been linked to aging and a number of age-onset neurodegenerative disorders, including Parkinson disease. Loss-of-function mutations in parkin, an E3 ubiquitin ligase that functions to promote the ubiquitin-proteasome system of protein degradation and also in mitochondrial quality control, have been implicated in heritable forms of Parkinson disease. The question of whether parkin can modulate aging or positively impact longevity, however, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
222
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(238 citation statements)
references
References 54 publications
12
222
2
1
Order By: Relevance
“…Protein aggregation is associated with many age-related disorders, and increased protein oxidation, mislocalization, and aggregation are observed in aged organisms [2][3][4][5][6][7]. Intuitively, these findings can be explained by a gradual decline in protein biosynthetic and quality control pathways and a progressive accumulation of protein damage.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Protein aggregation is associated with many age-related disorders, and increased protein oxidation, mislocalization, and aggregation are observed in aged organisms [2][3][4][5][6][7]. Intuitively, these findings can be explained by a gradual decline in protein biosynthetic and quality control pathways and a progressive accumulation of protein damage.…”
mentioning
confidence: 93%
“…Despite this, why organisms age remains a complex mystery that if understood could have profound implications for the quality of human health. While the physiological decline associated with old age is easily recognizable, the mechanisms that determine aging are poorly understood; however, widescale loss of protein homeostasis (proteostasis) is proposed to be one of the "primary hallmarks of aging" [1].Protein aggregation is associated with many age-related disorders, and increased protein oxidation, mislocalization, and aggregation are observed in aged organisms [2][3][4][5][6][7]. Intuitively, these findings can be explained by a gradual decline in protein biosynthetic and quality control pathways and a progressive accumulation of protein damage.…”
mentioning
confidence: 99%
“…It has been reported that PARK2 overexpression increases mitochondrial activity during aging in association with life-span extension, further supporting the notion that PARK2 has a pivotal role in mitochondrial quality control in terms of regulation of senescenceassociated disorders. 31 However, the precise mechanism for the decrease in PARK2 levels in COPD lung remains unclear. Furthermore, several lines of evidence demonstrate the participation of other receptors during autophagosomal recognition of mitochondria, including BNIP3L, BNIP3, and FUNDC1, hence the potential involvement of those receptors in mitophagy regulation of cigarette-induced cellular senescence need to be examined in future studies.…”
Section: Wwwtandfonlinecommentioning
confidence: 99%
“…An ominous consequence of proteostasis disruption is the accumulation of aggregated proteins, thereby accelerating cellular aging and increasing the risk of disease. Indeed, protein aggregation is associated with many age-related disorders, and increased protein oxidation and aggregation are observed in aged organisms (Knoefler et al 2012;Morimoto 2008;Rana et al 2013). An even greater challenge to proteostasis would occur if proteins were to aggregate into hyper-stable/degradation-resistant species, as these would be more likely to persist and further compromise the organism.…”
Section: Introductionmentioning
confidence: 99%